Evaluation of visual evoked potentials in children with headache - Akin, Ridvan; Unay, Bülent; Sarici, S Umit; Ulaş, Umit; Gökçay, Erdal (The Turkish Journal of Pediatrics, 2005)
Headache is a common problem in childhood. Visual evoked potential (VEP) P100 latencies were recorded in children with headache. Sixty-four patients, aged 10.7 +/- 1.2 years, met the criteria of the International Headache Society for the diagnosis of migraine. Fifty-eight patients, aged 10.2 +/- 1.3 years, with tension headache and 56 healthy subjects, aged 10.3 +/- 1.3 years, as the control group were also studied. Patients with migraine had slightly longer P100 latencies than the other two groups. We conclude that VEP latency recording is a valuable test in the diagnosis of migraine, and can be safely used in children.